2014
DOI: 10.1371/journal.pone.0093586
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Related Brain Damage in Humans

Abstract: Chronic excessive alcohol intoxications evoke cumulative damage to tissues and organs. We examined prefrontal cortex (Brodmann’s area (BA) 9) from 20 human alcoholics and 20 age, gender, and postmortem delay matched control subjects. H & E staining and light microscopy of prefrontal cortex tissue revealed a reduction in the levels of cytoskeleton surrounding the nuclei of cortical and subcortical neurons, and a disruption of subcortical neuron patterning in alcoholic subjects. BA 9 tissue homogenisation and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 52 publications
9
35
1
3
Order By: Relevance
“…Drugs of abuse have also been associated with proteasome inhibition which seems to be a key player in epigenetic mechanisms underlying the accumulation of oxidatively damaged histones [73]. In this frame, recent finding showed that ethanol exposure reduced intracellular 20S proteasome chymotrypsin-like activity in SH-SY5Y cells [74], in agreement with findings obtained in liver and brain demonstrating that ethanol decreased proteasome activity by interfering with 20S-CP (core particle) and 19S-RP (regulatory particle) assembly [75,76]. By contrast, cocaine has been reported to exert an opposite effect on the 20S proteasome, since the chymotrypsin-like activity [74] increases.…”
Section: Taking Advantage Of Neuroblastoma Cells: Versatile Model Forsupporting
confidence: 70%
“…Drugs of abuse have also been associated with proteasome inhibition which seems to be a key player in epigenetic mechanisms underlying the accumulation of oxidatively damaged histones [73]. In this frame, recent finding showed that ethanol exposure reduced intracellular 20S proteasome chymotrypsin-like activity in SH-SY5Y cells [74], in agreement with findings obtained in liver and brain demonstrating that ethanol decreased proteasome activity by interfering with 20S-CP (core particle) and 19S-RP (regulatory particle) assembly [75,76]. By contrast, cocaine has been reported to exert an opposite effect on the 20S proteasome, since the chymotrypsin-like activity [74] increases.…”
Section: Taking Advantage Of Neuroblastoma Cells: Versatile Model Forsupporting
confidence: 70%
“…There were no significant differences in the optical densities of the actin band between the diagnostic groups. Other researchers have not found significant differences in the intensity of western blot actin bands in the PFC (Flatscher-Bader and Wilce, 2008; Erdozain et al, 2014) or locus coeruleus (Karolewicz et al 2008) of human alcoholics as compared to non-alcohol abusing comparison subjects.…”
Section: Methodsmentioning
confidence: 89%
“…Methylation was initiated by the addition of PIMT and incubation for 30 minutes at 30°C, and terminated by adding 1 ml of ice-cold 7 % (w/v) trichloroacetic acid (TCA). Protein precipitated in the presence of TCA was sequentially washed and redissolved in 100 μl of 88 % (v/v) formic acid as described previously [17] to remove extraneous 3 H-SAM. The protein precipitate was finally solubilised in 100 μl of 0.5 M NaOH, 1 % (v/v) methanol, 5 % (v/v) Triton X-100, and transferred to 10 ml of scintillant and counted for radioactivity incorporation using a Packard Tri-Carb counter.…”
Section: Methodsmentioning
confidence: 99%